Pengaruh Pemasaran Media Sosial pada Brand Equity dan Brand Attitude yang mempengaruhi Purchase Intention pada aplikasi Shopee - Deni Wardani (STIE Indonesia Banking School, 2023)
The purpose of this study is to examine the influence of Firm Created Communication and User Generated Communication on Brand Attitude, then test Firm Created Communication, User Generated Communication, and Brand Attitude on Brand Equity. Next to test Brand Attitude and Brand Equity against Purchase Intention. The exogenous variables in this study are Firm Created Communication and User Generated Communication. While the endogenous variables in this study are Brand Attitude, Brand Equity and Purchase Intention. This research was conducted at the Shopee marketplace. The sample in this study used 50 respondents using the Shopee marketplace and the method used was Partial Least Square (PLS). The results of the conclusions of this study are as follows: 1) Firm Created Communication has a significant positive effect on Brand Equity, 2) User Generated Content does not have a significant positive effect on Brand Equity, 3) Brand Attitude has a significant positive effect on Brand Equity ,4) Firm Created Communication has no significant effect on Brand Attitude. 5) User Generated Content has a significant positive effect on Brand Attitude, 6) Brand Equity has a significant positive effect on Purchase Intention, 7) Brand Attitude has a significant effect.